Comparison between the Biological Active Compounds in Plants with Adaptogenic Properties (Rhaponticum carthamoides, Lepidium meyenii, Eleutherococcus senticosus and Panax ginseng) - Velislava Todorova; Kalin Ivanov; Stanislava Ivanova (Plants, 2021)
Background: In the 1960s, research into plant adaptogens began. Plants with adaptogenic properties have rich phytochemical compositions and have been used by humanity since ancient times. However, it is not still clear whether the adaptogenic properties are because of specific compounds or because of the whole plant extracts. The aim of this review is to compare the bioactive compounds in the different parts of these plants. Methods: The search strategy was based on studies related to the isolation of bioactive compounds from Rhaponticum carthamoides, Lepidium meyenii, Eleutherococcus senticosus, and Panax ginseng. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Results: This review includes data from 259 articles. The phytochemicals isolated from Rhaponticum carthamoides, Lepidium meyenii, Eleutherococcus senticosus, and Panax ginseng were described and classified in several categories. Conclusions: Plant species have always played an important role in drug discovery because their effectiveness is based on the hundreds of years of experience with folk medicine in different nations. In our view, there is great potential in the near future for some of the phytochemicals found in these plants species to become pharmaceutical agents.